EXPLORING THE FUNCTIONS OF IMPLICATURES IN NORTHERN KURMANJI - Jawzal, Nechirvan; Mohammed , Fakhir (Humanities Journal of University of Zakho, 2025)
The current paper explores the functions of implicatures in Northern Kurmanji (NK). It lays concentration on the non-literal meanings (interpretation) that speakers convey beyond the literal one of either their speech or writing. Data were collected through purposive sampling from senior university students in experimental and control groups. The participants were chosen for their availability and willingness to participate. They self-recorded informal conversations to explore various functions of implicature, including explanation, criticism, empathy, contemplation, and humor. There was identification of the reasons behind implicatures, which included explanation, criticism, empathy, philosophical contemplation, and humor. The results dictate that, in one hand a strategic use of implicatures was utilized by the control group. The participants of the control group often employed implicatures to help with expressing deeper emotional and philosophical engagement. On the other hand, the experimental group used implicatures mainly for functions related to immediate and practical social exchanges. It is also found that the functions of implicatures in NK represents the cultural and contextual dynamics which denotes communicative strategies of the NK. Further studies can be explored to identify the role of implicatures in modern digital communication and to compare data across different Kurdish dialects and sociocultural contexts.